The Role Of Motivation In Language Learning - Anwar Rahman (LINGUISTIKA, 2011)
The mastery of English learning is influenced by some variables, one of them is motivation. Motivation in learning second language is classified as integrative motivation and instrumental motivation. Some experts of language teaching also categorized motivation into two types namely intrinsic motivation and extrinsic motivation. This paper discusses about kinds of motivation and how it takes a role in influencing students mastery in learning language. It was literature study that focused to find out some solutions of students problem in learning language, especially learning language motivation which was interpreted and conducted at the State Polytechnic of Lampung. The result shows that intrinsic motivation and instrumental motivation have great influence in the success of language learning.